DEGRADASI LIMBAH AGROINDUSTRI (HATI NANAS DAN KULIT SINGKONG, KAKAO, PISANG, NANAS) DENGAN ENZIM SELULASE - , THERESIA ARUMSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agricultural wastes contain lignocellulose components consisting cellulose, hemicellulose, and lignin. Cellulose can be converted into glucose using cellulase enzymes. Glucose resulted from the process will be able to be used as material for bioethanol production. The ease of cellulosic hydrolysis in agricultural waste varies depending on the crystallinity of cellulose and the existance of lignin and hemicellulose within the waste. The study was conducted by analyzing the initial lignocellulosic composition of each wastes and the cellulose crystallinity index of the waste. To determine the level of ease of hydrolysis of cellulose, the Cassava Peel, Cocoa Peel (Pod), Banana Peel, Pineapple Peel and Pineapple Core are hydrolyzed by commercial cellulase enzyme âcelluclastâ with activity of 100 FPU/ml at a temperature of 50oC for 72 hours. The results showed that lignin has major role to hold up cellulose hydrolyzed rather than hemicellulose and cellulose crystallinity index. Sample with the highest level of hydrolysis ease is the pineapple core with a value of % CCR (Cellulose Conversion Ratio) 87.34. While the sample with the highest glucose production is pineapple peel with 152.4 g of glucose/kg of waste.